Pengaruh Pengetahuan Lingkungan, Kesadaran Lingkungan, dan Penggunaan Media Sosial Terhadap Perilaku Konsumsi Berkelanjutan pada Generasi Z di DKI Jakarta - Tasya Fadia; Dicky Iranto; Siti Fatimah Zahra (Indonesia Economic Journal, 2025)
The global environmental crisis demands more responsible and sustainable consumption patterns, especially among younger generations such as Generation Z. This study aims to analyze the influence of environmental knowledge, environmental awareness, and social media use on sustainable consumption behavior among Generation Z in DKI Jakarta. This study employs a quantitative approach with a causal-associative design. The sampling technique uses purposive sampling with a sample size of 130 respondents. Data were collected through an online questionnaire using a 1–5 Likert scale and analyzed using multiple linear regression with the assistance of SPSS. The results indicate that all independent variables have a positive and significant influence on sustainable consumption behavior. These findings reinforce the Theory of Planned Behavior (Ajzen, 1991) and confirm that cognitive (knowledge), affective (awareness), and social-digital (social media) dimensions play a crucial role in shaping pro-environmental behavior.